2020
DOI: 10.1186/s12888-020-02908-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between increased neutrophil-to-lymphocyte ratio and postoperative delirium in elderly patients with total hip arthroplasty for hip fracture

Abstract: Background Delirium is a common complication in elderly patients with total hip arthroplasty (THA) for hip fracture. The mechanism of postoperative delirium (POD) is associated with the neuroinflammatory process. The aim of this study was to the incidence and perioperative risk factors of POD and investigate whether NLR could serve as a potential marker for POD in elderly patients with THA for hip fracture. Methods This was a multicenter prospective study, we included elderly patients with THA for hip fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 52 publications
0
44
0
Order By: Relevance
“…A small pilot study revealed that an increased NLR in acutely ill patients was associated with delirium [ 10 ], and it was proposed that the preoperative NLR can be regarded as a potential marker for the prediction of early-onset delirium after acute ischemic stroke [ 23 ]. A prospective multicenter observational study revealed that a higher preoperative NLR was an independent predictor of POD in patients who underwent total hip arthroplasty [ 14 ]. Two observational studies regarding delirium after cardiac surgery showed that an increased postoperative NLR was associated with POD [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small pilot study revealed that an increased NLR in acutely ill patients was associated with delirium [ 10 ], and it was proposed that the preoperative NLR can be regarded as a potential marker for the prediction of early-onset delirium after acute ischemic stroke [ 23 ]. A prospective multicenter observational study revealed that a higher preoperative NLR was an independent predictor of POD in patients who underwent total hip arthroplasty [ 14 ]. Two observational studies regarding delirium after cardiac surgery showed that an increased postoperative NLR was associated with POD [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association between an increased NLR and poor prognosis of various cardiovascular diseases [ 8 , 9 ] and malignancies [ 10 ]. A pilot study showed that the NLR was increased in acutely ill patients with delirium [ 11 ], and several studies showed that a higher preoperative NLR may be associated with the development of POD in patients undergoing cardiac surgery [ 12 ], carotid endarterectomy [ 13 ], and total hip arthroplasty [ 14 ]. In contrast, Ida and colleagues did not find a significant association between POD and the preoperative NLR [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our WBC count findings extend the results of previous articles showing abnormal immune-inflammatory responses including increased NLR levels in patients with delirium (see Introduction). For example, Egberts and Mattace-Raso [19] in 2017, Kotfis et al [20] in 2019, and He et al [21] 2020 reported significant positive correlations between an elevated NLR and the emergence of delirium in various patient settings. NLR is relevant index which is useful in surgical emergencies, postoperative complications, and inflammatory conditions [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…By far as we know, there has been no study to investigate the incidence and risk factors of postoperative AIS in patients≥70 years old with THA for hip fracture. By comparison, there are more studies on postoperative delirium [ 13 15 ], postoperative pneumonia [ 16 18 ]. However, with the aggravation of aging in the worldwide, the rising number of THA being performed in elder patients annually, risk factors related to postoperative AIS in these elderly patients should be considered.…”
Section: Introductionmentioning
confidence: 99%